Semantic and Structural Differentiation of Euphemisms - Hilola Ismailova Inomovna (Zien Journals, 2022)
The current article is devoted to the study of semantic and structural Differentiation of Euphemisms. It discusses the differences and similarities of euphemisms in the sphere of business, diseases and medicine. Euphemisms are used to replace social taboos, swearing, blasphemy, profanity and other offensive language, but they can be used just to make a common word sound more sophisticated. For indirect expressing, stylistic means like figures of speech can be used for expressing euphemisms. Another subject mentioned in the paper is euphemistic strategies discussed from pragmatic point of view.
Keywords: offensive; vague; phenomenon; euphemisms